Thermal efficiency of radiated tetra-hybrid nanofluid [(Al2O3-CuO-TiO2-Ag)/water]tetra under permeability effects over vertically aligned cylinder subject to magnetic field and combined convection - Adnan; Abbas, Waseem; Z. Bani-Fwaz, Mutasem; Kenneth Asogwa, Kanayo (Science progress (1916), 2023)
Applications The nanofluids and their upgraded version (ternary and tetra nanofluids) have a very rich thermal mechanism and convinced engineers and industrialist because of their dominant characteristics. These broadly use in chemical, applied thermal, mechanical engineering, and biotechnology. Particularly, heat transfer over a cylindrical surface is important in automobiles and heavy machinery. Purpose and Methodology Keeping in front the heat transfer applications, a model for Tetra-Composite Nanofluid [(Al2O3-CuO-TiO2-Ag)/water]tetra is developed over a vertically oriented cylinder in this study. The existing traditional model was modified with innovative effects of nonlinear thermal radiations, magnetic field, absorber surface of the cylinder, and effective thermophysical characteristics of tetra nanofluid. Then, a new heat transfer model was achieved successfully after performing some mathematical operations. Major Findings The mathematical analysis was performed via RK and determined the results graphically. The study gives suitable parametric ranges for high thermal efficiency and fluid movement. Applied magnetics forces were observed excellent to control the fluid motion, whereas curvature and buoyancy forces favor the motion. Thermal mechanism in Tetra nanofluid is dominant over ternary nanoliquid and nonlinear thermal radiations increased the heat transfer rate.